Magnetization Estimation Technique of Permanent Magnets Loaded on Rotor of IPMSM Using Actual Measurement Value of Leakage Flux - Narichika Nakamura; Masahide Shioyama; Yoshifumi Okamoto (IEEE Access)
The production of mass-produced permanent magnet synchronous motors (PMSMs) includes a post-assembly magnetization process. Given that the performance of PMSMs is contingent upon the magnetization quality of the permanent magnets (PMs), the estimation of PM magnetization emerges as a crucial procedure. While various magnetization estimation methods for pre-assembly magnetization have been proposed, no method has been proposed for post-assembly magnetization to estimate the magnetization distribution of PMs loaded onto the rotor core of PMSMs. This study introduces the magnetization estimation technique using the leakage flux derived from the magnetic circuit (MELF). MELF stands out because it can estimate the magnetization distribution of PMs without the need for prior magnetization data. This innovative approach employs a gradient-based optimization method, incorporated with input data composed of accurate measurement values, facilitating fast and detailed estimations. The performance of the proposed method (MELF) is verified using the actual rotor of IEEJ D-model, which serves as one of the benchmark models of interior permanent magnet synchronous motors (IPMSMs).